Pengaruh Likuiditas, Struktur Modal dan Aktivitas Terhadap Profitabilitas Perusahaan Manufaktur Sub Sektor Pakan Ternak di Bursa Efek Indonesia - apriati octorika apri; Bakti Setyadi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
The campany basically, it cannot be separated from the goal, namely to obtain maximum profit. Profitability for the company plays an important role in maintaining its survival. Increasing company profitability can be influenced by several factors such as liquidity, capital structure and activity. The purpose of this study was to determine the effect of liquidity, capital structure, and activity on profitability in animal feed sub-sector manufacturing companies on the Indonesia Stock Exchange. This research approach is an associative quantitative approach with a causal nature. The data used in this study is secondary data, namely the financial statements of manufacturing companies in the animal feed sub-sector on the Indonesia Stock Exchange for the 2017-2020 period. The analytical technique used in this research is descriptive statistical test, classical assumption test, and multiple linear regression analysis. Based on the analysis results show that partially liquidity has no significant effect on profitability, capital structure has no significant effect on profitability, and activity does not have a significant effect on profitability while simultaneously liquidity, capital structure and activity have a significant effect on profitability.